OPTIMALISASI PEMBELAJARAN MELALUI PELAKSANAAN LESSON STUDY - Sri Wahyuni (Jurnal Pendidikan Almuslim, 2016)
The aimed of this article at discussing of implementing lesson study to increase the teaching and learning. Lesson study was implemented on methodology lesson at the second semester in 2011/ 2012 and evaluation lesson at the first semester in 2012/2013. The techniques of data collection are observation and field note. The steps of lesson study consist of Plan, Do, See (Reflection) cycle are 1) lesson plan emphasize on student active learning; 2) Action plan (Do) will be good because has already done prepare a good lesson plan and learning will be good the next learning as suistanable; 3) See (Reflection) shown flash back from implementation of lesson study and receive good inputs for the next learning from obsevers.  Lesson Study ought to conducted for the next two batch and then the lesson study will be continue by Almuslim Universitye. Keywords:          Lesson study, plan, do, see